Code-Mixing Found in Scarlett Whitening Instagram Posts - Ni Made Mutiara Deca Sagitarini; I Gde Agoes Caskara Surya Putra (Universitas Sebelas Maret, 2023)
This study focused on the code-mixing phenomenon discovered in an Instagram post by Scarlett White. The Instagram post of Scarlett Whitening was recently featured as one of the most popular beauty products in Indonesia. This research seeks to determine the various types of code-mixing in Scarlett Whitening's Instagram posts, as well as the most prevalent types and the reasons why they are used. For the purpose of data analysis, a qualitative descriptive method was employed in this study. Analysis of the data revealed three types of Code-mixing: intrasentential mixing, intra-lexical mixing, and changes in pronunciation. Moreover, code-mixing occurs for three reasons: discussion of a particular subject, interjection, and the desire to clarify the speech content for the interlocutor.